Do cows see the forest or the trees? A preliminary investigation of attentional scope as a potential indicator of emotional state in dairy cows housed with their calves - Neave, Heather W.; Rault, Jean-Loup; Bateson, Melissa; Jensen, Emma Hvidtfeldt; Jensen, Margit Bak (Frontiers in Veterinary Science, 2023)
A positive mood in humans tends to broaden attentional scope while negative mood narrows it. A similar effect may be present in non-human animals; therefore, attentional scope may be a novel method to assess emotional states in livestock. In this proof-of-concept exploratory study, we examined the attentional scope of dairy cows housed with their calves either full-time, part-time (during daytime only), or with no calf contact (enrolled n=10 each). Housing conditions were previously verified to induce positive and negative emotional states, where part-time was considered more negative. Cows were trained to approach or avoid hierarchical images on a screen that were consistent in local and global elements (i.e. 13 small circles or crosses arranged in an overall circle or cross). After discrimination learning (>80% correct, over two consecutive days), 14 cows proceeded to test (n=6 each full- and part-time; n=2 no-contact, not analyzed). Test images showed inconsistent combinations of global and local elements (i.e. the overall global shape differs from the smaller local elements, such as a global circle composed of smaller local crosses and vice versa). Over two test days, approach responses to global and local images (each presented four times) were recorded. All cows were more likely to approach the local than the global image, especially part-time cows who never approached the global image; this may reflect a narrowed attentional scope in these cows. Full-time cows approached images more often than part-time cows, but overall response rates to global and local images were low, making specific conclusions regarding attentional scope difficult. Different housing conditions have potential to affect attentional scope, and possibly emotional state, of dairy cows, but statistical comparison to no-contact treatment was not possible. Arousal (cortisol concentration) due to treatment or test conditions could not explain test performance. Further work with refined methodology and a larger sample size is required to validate the reliability of attentional scope as an assessment method of emotional state in cattle. Beyond this, the attentional scope test revealed how cattle may process, learn and respond to different visual hierarchical images, which further our understanding of cognitive and visual processes in cattle.